ANALISIS MODAL INTELEKTUAL DAMPAKNYA TERHADAP KINERJA KARYAWAN PADA PT. ADV SEKURINDO - Rosgandika Mulyana; Taufik Nughraha (JURISMA : Jurnal Riset Bisnis & Manajemen, 2013)
An intellectual capacity of an organization's human resources can be seen from its employee's competency quality, organization’s commitment, and assignment control. In an organization or a company, the employee's intellectual capital is very important because it will increase the employee’s performance and can help the company to achieve its aims. The purpose of the research is to analyze intellectual capital’s impacts on employee’s performance at PT. ADV SEKURINDO. This research uses descriptive and verification methods with quantitative approach. The descriptive method is used to find out employee’s intellectual capital and performance The verification method is used to find out the intellectual capital’s impact on the employee’s performance at PT. ADV SEKURINDO. This research is a census of 75 employees as the analysis’ object. The technique of data collection is done by observing, documenting, questioning, and interviewing. The quantitative analysis is done using correlation, double regression, and determination, also testing the hypothesis using SPSS 13 For Windows.The result of the research shows that the intellectual capital is included in good category, but the employee’s performance is in fair category. The result of the research shows that the intellectual capital simultaneously and partially gives significantly impacts (α = 0,05) on the employee's performance which results closeness relation level (0.677) and the impact’s scale is 45.8 %, The employee's performance is determined by the intellectual capital, which consists of competency, organization’s commitment, and assignment control. For the rest, 54.2%, is influenced by other factors. The superior impact on the employee’s performance of the three factors is competency, but the inferior factor is commitment.         Keywords: Intellectual Capital’s, Competency, Organization’s Commitment,        Assignment Control and Employee’s Performance.